CORM: An R Package Implementing the Clustering of Regression Models Method for Gene Clustering: Supplement Issue: Array Platform Modeling and Analysis (A). (January 2014) - Shi, Jiejun; Qin, Li-Xuan
We report a new R package implementing the clustering of regression models (CORM) method for clustering genes using gene expression data and provide data examples illustrating each clustering function in the package. The CORM package is freely available at CRAN fromhttp://cran.r-project.org .